DEVELOPMENT OF A GUIDEBOOK FOR INVESTING THE CHARACTER VALUE OF ELEMENTARY SCHOOL STUDENTS IN CLASS IV OF SDN 1 HANTARA - Myrna Apriany Lestari; Febby Fajar Nugraha; Fanni Rachmawati (Journal Of Educational Experts (JEE), 2023)
Character is a special characteristic that a person has which is individual and reflects a person's morals. Education today does not only develop cognitive aspects, but one of the most important aspects of development is religious and moral values. The cultivation of character values is very necessary to create a nation's successor with character and noble character. Instilling character values in students is not only the task of teachers at school, but also the task of parents at home. Parents at home can use the manual as a tool in its implementation. This research and development aims to describe a guidebook for inculcating appropriate character values in fourth grade students at SD Negeri 1 Hantara. This research uses research and development method (research and development) model Borg & Gall. The purpose of this study was to develop a guidebook product for character values cultivation and to determine the feasibility of the product. According to Borg & Gall, there are ten steps in research and development, which are simplified into three steps, namely (1) preliminary study, (2) product development, and (3) testing and dissemination. Based on the feasibility test assessment carried out on each indicator the average score of Aiken's V obtained is 0.87, it can be interpreted as a fairly high coefficient for each indicator in the guidebook for planting the character values of the fourth grade elementary school students. This means that the developed manual product has a very high level of validity. So the product of the developed guidebook is categorized as very feasible based on each indicator contained in the guidebook for planting the character values of fourth grade elementary school students.Â